Phosphorus release and retention by soils of natural isolated wetlands. (7th November 2006) - Dunne, E.J.; Reddy, K.R.; Clark, M.W.
Hydrological restoration of historically isolated wetlands may mitigate phosphorus (P) loss. The objectives of this study were to quantify P in soil, and to determine the effect of (1) soil characteristics on P release, and (2) antecedent soil hydrological conditions on P dynamics. Humic/fulvic acid bound P and residual P accounted for majority of P (>78%) in surface soils. Soils with highest nutrient status and labile P fractions released most P during initial flooding. Phosphorus dynamics during additional flooding were dependent on soil characteristics, antecedent soil hydrological conditions, and P levels in the water. Phosphorus retention varied between 0.3 and 8 mg m -2 d -1 .